Preface - Mohd. Noor, Faridah Noor (KATHA- The Official Journal of the Centre for Civilisational Dialogue, 2015)
The first four papers were presented at the Seminar of Malay and Chinese Philosophy of Sciences held at the Centre for Civilizational Dialogue, University of Malaya, in 2014 with collaboration of the Akademi Sains Islam Malaysia (ASASI).